Acquired type IIIa colonic atresia in a three-year-old child: A case report - Irene Austria-Ramos; Holly L. Green; Jaya Punati; Phillip Stanley; Christopher Gayer (Elsevier, 2023)
Introduction: A boy with chronic intestinal dysmotility and severe abdominal distention developed complete intestinal obstruction by age three. We present a unique case of acquired Type IIIa colonic atresia, likely as a progressive sequela from necrotizing enterocolitis (NEC). Case presentation: Born with suspected prune belly syndrome (PBS) and severe ileus, he was treated for NEC at one month of age. Prior to age three, he was hospitalized over 20 times for abdominal distention, vomiting and electrolyte derangements and treated with rehydration and stomach decompression. He passed stool infrequently and tolerated small amounts of formula by mouth for months at a time. A dysmotility workup at 23 months showed gastroparesis with abnormal antroduodenal motility and normal anorectal motility. Imaging at birth showed dilated bowel without obstruction. Radiographic imaging showed progression from ileus to stricture to obstruction over a 3-year period. At age three, exploratory laparotomy revealed Type IIIa colonic atresia in the transverse colon with complete mesenteric separation. The massive right colon was resected, and a diverting ileostomy created. He continues to have oral aversion, gastroparesis, and malabsorption due to pseudo-obstruction. Conclusion: The absence of a distal microcolon and the patent bowel on imaging done early in life, are compatible with acquired, instead of congenital, Type IIIa colonic atresia. Previously reported cases of acquired colonic atresia associated with NEC have been type I and found in infancy. An acquired colonic atresia with complete mesenteric separation is highly unusual. This is the first report of such a finding in a three-year-old child.